KEY DRIVERS AND CHALLENGES IN IMPLEMENTING THE DIGITAL PRODUCT PASSPORT (Eureka Journal of Business, Economics & Innovation Studies, 2026)
The article examines the digital product passport (DPP) as a strategic digital infrastructure for enterprises under modern digital and circular economy conditions, and provides a systematic analysis of the internal and external factors driving its implementation, as well as the main barriers and risks. Based on the analysis of the European Union’s regulatory and legal documents, as well as consulting and industry reports, the paper highlights the impact of DPP on digitalization, operational efficiency, competitive advantage, corporate reputation, and circular economy objectives. At the same time, it classifies key barriers such as problems of data interoperability and standardization, digitalization costs, shortages of technical and managerial skills, concerns related to data collection and security, and resistance to organizational change. The research findings show that DPP should be viewed as a core mechanism for transitioning to sustainability, transparency, and innovative business models, while its successful implementation requires the development of standardization, strengthening human capacity, and enhancing cooperation among stakeholders.
Keywords: Digital product passport (DPP), circular economy, digital identification, sustainability, digital transformation, Industry 4.0, blockchain, supply chain transparency.